Improving Student Learning Outcomes Through The Application of A Cooperative Learning Model with A Shopping Window Setting - Lisa Aditya Dwiwansyah Musa; Hardianto Hardianto; Muhammad Firdaus Nur (Green Publisher Indonesia, 2022)
This study aims to improve student learning outcomes through the application of cooperative learning models with window shopping settings. This research is a classroom action research conducted in two cycles. The subjects in this study were mathematics education students at one of the tertiary institutions in Palopo City. Data was collected through student activity observation sheets and student learning outcomes tests, which were then processed through descriptive statistics. The results showed that there was an increase in the average score of student learning outcomes from cycle I to cycle II, increased student learning completeness from cycle I to cycle II, and increased student learning activity from cycle I to cycle II, so it can be concluded that the application of the cooperative learning model window shopping settings can improve student learning outcomes